Radio broadcasting in Palmerston North, 1924-1937 : a research exercise... Bachelor of Arts with Honours in History at Massey University - Fleming, Philip J (Massey University, 1980)
The 1920s and 1930s were a period when many new developments were taking place in the field of leisure and entertainment, like the rise of the motor car and the emergence of the 'talking picture'. The introduction of radio broadcasting was, perhaps, one of the most important of these developments. New Zealanders took up the new medium with eagerness and from the plaything of a few enthusiastic amateurs, it developed into an integral part of community life. In +-1921, for example, there were 2,830 radio licenses issued yet by 1934 there were 118,086 licenses current and by 1936 the total had risen to 192,265. This increased interest in radio reflected, to a considerable extent, improvements in the quality, coverage and organization of the Dominion's national radio stations. I would suggest, however, that the B class stations, small stations privately operated by groups of amateurs and radio dealers, played a vital role in introducing the new medium of radio to the community, a role which will be elucidated in the following pages. [From Introduction]